A multi-isotope (C, N, O, Sr, Pb) study of Iron Age and Roman period skeletons from east Edinburgh, Scotland exploring the relationship between decapitation burials and geographical origins. (February 2020) - Moore, Joanna; Rose, Alice; Anderson, Sue; Evans, Jane; Nowell, Geoff; Gröcke, Darren R.; Pashley, Vanessa; Kirby, Magnus; Montgomery, Janet
Abstract: Recent excavations at Musselburgh, East Lothian (Scotland) revealed twelve skeletons, radiocarbon dated to the Iron Age and Roman period. The high incidence of skeletal trauma characteristic of decapitation in those of Roman date makes this site unusual. A multi-isotope investigation of seven of these individuals was conducted to explore any link between intrusive burial practices and migration at one of Britain's most northerly frontiers. Bulk collagen analysis provided a terrestrial, C3, dietary protein signal (mean δ 13 C −20.4‰ and δ 15 N + 11.1‰), consistent with other Romano-British studies. However, the range of δ 18 O, 87 Sr/ 86 Sr and Pb isotopes indicate more diverse origins for the Roman individuals. These results suggest that decapitation burials were afforded to migrants to the Lothian area, but is not indicative of a common origin, implying that something more complex than a shared geographic childhood origin united these individuals. The possible association of these decapitation burials with a nearby 2nd century fort suggests that they may also represent some of the earliest examples of Roman decapitation burials to be found anywhere in Britain.